Efficient cogeneration and district heating systems in bioenergy villages: an optimization approach. (1st October 2015) - Karschin, Ingo; Geldermann, Jutta
Abstract: The availability of renewable energy sources and highly efficient technologies are two major considerations when evaluating a sustainable energy supply with low carbon emission. Bioenergy villages combine the use of biomass as a renewable energy source with the efficient cogeneration of heat and power. The planning of these bioenergy villages using biomass as a source of electricity and heat calls for the simultaneous identification of facility location, capacity planning, and network design for the heating grid. A linear mathematical model is presented, that optimizes the local bioenergy production and distribution system and considers various parameters such as biomass availability, the number of heat customers, or heat loss in the system. The model is applied and validated using a case study in a small village in Lower Saxony (Germany).